PENULISAN NASKAH DENGAN TEKNIK DESKRIPTIF DALAM PRODUKSI DOKUMENTER BIOGRAFI “PISAU BATIK MR. DIMAN” - Fanni Annisa Putri; Dwi Nurrahmi Kusumastuti; Imam Subechi (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACT Biographical documentaries are documentaries that relate to stories someone's life. Biographical documentaries tell the story of a well-known person broad, has greatness, uniqueness, or other interesting aspects. On The documentary entitled "Mr. Diman's Batik Knife" tells the story of the knife's creator Metal batik is Mr. Sudiman who comes from Krengseng Village, Kalirandu, Bangunjiwo, Kasihan, Bantul. The aim of making this documentary program is: to find out the background of the character who found the idea to make batik knife medium. In this documentary work the author acts as a script writer, Responsible for creating the script with the director. Writer uses descriptive techniques in this documentary program to provide a factual and accurate description of the object being investigated. Technique The descriptive method used is in the form of observations carried out directly with observe, record and see directly how the daily lives of the characters and also batik knife production process. By using descriptive techniques the author can gain a lot information, so that the manuscript presented is in accordance with the techniques used director is expository, therefore this documentary can be used as media of information and delivery of messages that are interesting and can be consumed various groups. Key words: documentary, scriptwriter, descriptive technique.